Kinetics of Glycoprotein-Specific Antibody Response in Patients with Severe Fever with Thrombocytopenia Syndrome - Hyemin Chung; Eunsil Kim; Bomin Kwon; Yeong-Geon Cho; Seongman Bae; Jiwon Jung; Min-Jae Kim; Yong-Pil Chong; Sung-Han Kim; Sang-Oh Lee; Sang-Ho Choi; Yang-Soo Kim; et al. (Viruses, 2022)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tickborne disease in East Asia that is causing high mortality. The Gn glycoprotein of the SFTS virus (SFTSV) has been considered to be an essential target for virus neutralization. However, data on anti-Gn glycoprotein antibody kinetics are limited. Therefore, we investigated the kinetics of Gn-specific antibodies compared to those of nucleocapsid protein (NP)-specific antibodies. A multicenter prospective study was performed in South Korea from January 2018 to September 2021. Adult patients with SFTS were enrolled. Anti-Gn-specific IgM and IgG were measured using an enzyme-linked immunosorbent assay. A total of 111 samples from 34 patients with confirmed SFTS were analyzed. Anti-Gn-specific IgM was detected at days 5–9 and peaked at day 15–19 from symptom onset, whereas the anti-NP-specific IgM titers peaked at days 5–9. Median seroconversion times of both anti-Gn- and NP-specific IgG were 7.0 days. High anti-Gn-specific IgG titers were maintained until 35–39 months after symptom onset. Only one patient lost their anti-Gn-specific antibodies at 41 days after symptom onset. Our data suggested that the anti-Gn-specific IgM titer peaked later than anti-NP-specific IgM, and that anti-Gn-specific IgG remain for at least 3 years from symptom onset.